OpenPCI: Um toolkit para atender os requisitos técnicos do PCI DSS - Dapper, Fábio Juliano; Fagundes, Leonardo Lemes (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2009: Companion Proceedings of the 9th Brazilian Symposium on Information and Computational Systems SecurityDO - 10.5753/sbseg_estendido.2009.20636, 2009)
This article does not have an abstract.